The Effect of Institutional Ownership, Managerial Ownership and Deferred Tax Expense on Earnings Management in Indonesia - Kusumawardhani, Indra; Murdianingrum, Sri Luna (RSF Conference Series: Business, Management and Social Sciences, 2021)
The goal of this research was to see how Institutional Ownership, Managerial Ownership, and Deferred Tax Expense affected Earnings Management. In this study, 811 non-financial businesses listed on the Indonesia Stock Exchange from 2017 to 2019 were used as a sample. The independent factors in this study were Institutional Ownership, Managerial Ownership, and Deferred Tax Expense, while the dependent variable was Earnings Management. Multiple linear regression analysis was used to analyze the data in this study. This study's findings suggest that institutional and managerial ownership have an impact on earnings management. The Variable for Deferred Tax Expenses has no effect.